Prevalence of Erectile and Ejaculatory Difficulties among Men in Croatia - Štulhofer, Aleksandar (Array, 2006)
Aim. To determine the prevalence and risk factors of erectile difficulties and rapid ejaculation in men in Croatia. Method. We surveyed 615 of 888 contacted men aged 35-84 years. The mean age of participants was 54  ±   12 years. College-educated respondents and the respondents from large cities were slightly overrepresented in the sample. Structured face-to-face interviews were conducted in June and July 2004 by 63 trained interviewers. The questionnaire used in interviews was created for commercial purposes and had not been validated before. Results. Out of 615 men who were sexually active in the preceding month and gave the valid answers to the questions on erectile difficulties and rapid ejaculation, 130 suffered from erectile or ejaculatory difficulties. Men who had been sexually active the month before the interview and gave the valid answers to the questions on sexual difficulties reported having erectile difficulties more often (77 out of 615) than rapid ejaculation (57 out of 601). Additional 26.8% (165 out of 615) and 26.3% (158 out of 601) men were classified as being at risk for erectile difficulties and rapid ejaculation, respectively. The prevalence of erectile difficulties varied from 5.8% in the 35-39 age group to 30% in the 70-79 age group. The association between age and rapid ejaculation was curvilinear, ie, U-shaped. Rates of rapid ejaculation were highest in the youngest (15.7%) and the oldest (12.5%) age groups. Older age (odds ratios [OR], 6.2-10.3), overweight (OR, 3.3-4.2), alcohol (OR, 0.3-0.4), intense physical activity (OR, 0.3), traditional attitudes about sexuality (OR, 2.8), and discussing sex with one’ s partner (OR, 0.1-0.3) were associated with erectile difficulties. Education (OR, 0.1-0.3), being overweight (OR, 22.0) or obese (OR, 20.1), alcohol consumption (OR, 0.2-0.3), stress and anxiety (OR, 10.8-12.5), holding traditional attitudes (OR, 2.8) and moderate physical activity (OR, 0.1) were factors associated with rapid ejaculation. Conclusion. The prevalence of erectile difficulties was higher than the prevalence of rapid ejaculation in men in Croatia. The odds of having these sexual difficulties increased with older age, overweight, traditional attitudes toward sex, and higher level of stress and anxiety.